The political life of placeholders: poetics of sacrifice in digital video art - Willemars, Ilios Franciscus David Martin Ronald (UCP Press, 2026)
This book analyses how digital image production changes the way in which human beings identify themselves with and through visual and informational imagery. It traces the political implications of everyday processes of digitalization by confronting Franz Kafka’s literary work with contemporary digital video art by makers like Cécile B. Evans and Ed Atkins. Suggesting that a new reflection on the notion of sacrifice and poetics may be needed today more than ever, these analyses employ the concept of the placeholder to make sense of our representational episteme.